Pengetahuan Covid - 19 dan Penerapan Protokol Kesehatan Covid - 19 - Heni Ekawati; Ulva Noviana; M Hasinuddin; Mustofa Haris; Merlyna Suryaningsih (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
The health protocol is a series of rules issued by the government through the ministry of health in regulating the safety of activities during the Covid-19 pandemic by wearing masks, washing hands, maintaining distance, staying away from crowds, and reducing mobility. The purpose of this study is to analyze the relationship between knowledge about Covid-19 and the application of health protocols in children aged 10-12 years. This study used a cross-sectional design. The study population was 181 and a sample of 123 respondents using the Stratified Random Sampling technique. The research instrument uses a questionnaire with the Spearman rank test. The results showed that most of the respondents had less knowledge as many as 49 people with a percentage of 39.8%, most of the respondents did not implement health protocols as many as 54 people with a percentage of 43.9%. Analyzed with the Spearman rank test there was a relationship between knowledge about Covid-19 prevention and the application of health protocols for children aged 10-12 years. It is recommended that children increase their knowledge about Covid-19 prevention so that they can implement good health protocols to protect themselves and others from the dangers of Covid-19.